2013
DOI: 10.1007/s00192-013-2092-0
|View full text |Cite
|
Sign up to set email alerts
|

The use of transvaginal synthetic mesh for anterior vaginal wall prolapse repair: a randomized controlled trial

Abstract: Introduction and hypothesisThe aim of the study was to compare the efficacy and safety of transvaginal trocar-guided polypropylene mesh insertion with traditional colporrhaphy for treatment of anterior vaginal wall prolapse.MethodsThis is a randomized controlled trial in which women with advanced anterior vaginal wall prolapse, at least stage II with Ba ≥ +1 cm according to the Pelvic Organ Prolapse Quantification (POP-Q) classification, were randomly assigned to have either anterior colporrhaphy (n = 39) or r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
22
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 23 publications
6
22
3
Order By: Relevance
“…Only one patient (2.3%) was submitted to partial resection of the exposed mesh and primary suture of the vaginal margins. These data are in accordance to the literature, that range from 5 to 15% (17,19,21,22). The main limit of the present study was that it was performed in a single center and did not have an independent examiner during objective evaluations at the postoperatory period.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Only one patient (2.3%) was submitted to partial resection of the exposed mesh and primary suture of the vaginal margins. These data are in accordance to the literature, that range from 5 to 15% (17,19,21,22). The main limit of the present study was that it was performed in a single center and did not have an independent examiner during objective evaluations at the postoperatory period.…”
Section: Discussionsupporting
confidence: 91%
“…It was observed success rate of 55% of the anterior colporraphy group versus 87% of the mesh group, but both groups showed improvement of urinary and POP symptoms. Delroy et al (19) in a prospective, controlled and randomized trial treated women with AVWP using the same kit of the present study and showed an anatomical success (Point Ba < -1) in 82.5% in group Mesh and 56.4% in Control group at 12-month follow-up. The NNT was 4.…”
Section: Discussionsupporting
confidence: 69%
“…Only two of them (6.5%) report treatment failure after 12 months follow-up [12]. In the study of Delroy et al 79 women underwent either a classic anterior repair or a method using NAZCA TC but urinary incontinence was not analyzed in that study [35]. In our population in turn, the objective cure rate from SUI was 33%.…”
Section: Discussionmentioning
confidence: 64%
“…Urinary tract infections (UTI's) were noticed by 20% of patients. A statistically significant improvement was observed in all compartments but additional procedure for posterior or central compartment in more than 50% of women had to be performed [12,35].…”
Section: Discussionmentioning
confidence: 90%
“…In studies with apical fixation or concomitant apical surgery [71][72][73][74][75][76][77][78][79], anterior repair using a synthetic mesh (excluding Prolift ® and Perigee ® ) had a cumulative success rate of 93 %; the cumulative success rate of studies without apical fixation or without standard apical surgery [80][81][82][83][84][85][86][87][88][89] was 83 %. The cumulative rate of mesh erosion was 8 % (137/1740); the cumulative rate for chronic pain and de novo dyspareunia was 7% (59/846).…”
Section: Level Of Evidence 3 Grade Of Recommendation Bmentioning
confidence: 99%